Full slenderness range DSM approach for stainless steel hollow cross-section columns and beam-columns. (November 2017) - Arrayago, I.; Rasmussen, K.J.R.; Real, E.
Abstract: The behaviour of austenitic, ferritic and duplex stainless steel Rectangular and Square Hollow Section members subjected to compression and combined loading is investigated in this paper. A full slenderness range Direct Strength Method (DSM) approach is proposed based on experimental results and numerical strengths obtained from FE parametric studies. The method accounts for local buckling effects and enhanced material properties are also incorporated for those members stable enough to allow partial yielding of the cross-sections. The proposed method is based on strength curves previously provided for cross-sections although additional limitations have been adopted. The DSM approach for columns is based on existing buckling curves and provides accurate resistance predictions for slender and stocky cross-sections. The proposed DSM approach for beam-columns also improves capacity predictions for stocky and slender cross-sections obtained from the traditional methods for different bending moment distributions. This is attributed to the fact that the beam-column behaviour is directly calculated with a unique strength curve, considering the member and section slendernesses based on the elastic instabilities of the section subjected to the actual stress distribution instead of calculating the compressive and flexural strengths independently and combining these through an interaction equation, as is the traditional uncoupled approach. Finally, a reliability study of the full slenderness range DSM approach is presented to determine resistance factors for the different stainless steel grades columns and beam-columns. Highlights: A full slenderness range DSM approach for stainless steel SHS and RHS columns and beam-columns is proposed. The method considers strain hardening and local buckling effects and has been extended to beam-columns with non-uniform bending distribution. The method is assessed for different buckling curves and interaction expressions. The new approach has been statistically validated and provides more accurate results than traditional methods.